A survey on indigenous utilization and nutritional value of sasing (Sipunculus nudus) in Brgy. Balaring, Silay City, Negros Occidental - Tayona, Mary Lorraine Velasco (SOTECH, 2006)
People living in Brgy. Balaring, Silay City, Negros Occidental utilize a species of marine worm, locally known as sasing, for food.